In vitro Radiopharmaceutical Evidence for MCHR1 Binding Sites in Murine Brown Adipocytes - Balber, Theresa; Benčurová, Katarína; Kiefer, Florian Wolfgang; Kulterer, Oana Cristina; Klebermass, Eva-Maria; Egger, Gerda; Tran, Loan; Wagner, Karl-Heinz; Viernstein, Helmut; Pallitsch, Katharina; Spreitzer, Helmut; Hacker, Marcus; et al. (Frontiers in Endocrinology, 2019)
[11C]SNAP-7941 and its radiofluorinated, fluoro-ethyl derivative [18F]FE@SNAP have been developed as the first positron emission tomography tracers for melanin-concentrating hormone receptor 1 (MCHR1) imaging. Accumulation of these MCHR1 PET-tracers in rat brown adipose tissue (BAT) in vivo provided first indication of MCHR1 expression in rodent BAT. To rule out off-target binding, affinity of both MCHR1 ligands towards adrenergic beta-3 receptors (ADRB3) was examined. Further, specific binding of [11C]SNAP-7941 to brown adipocytes and effects of MCHR1 ligands on brown adipocyte activation were investigated. SNAP-7941 and FE@SNAP evinced to be highly selective towards MCHR1. [11C]SNAP-7941 binding to brown adipocytes was shown to be mainly MCHR1-specific. This data strongly indicates MCHR1 expression in rodent BAT and moreover, a peripheral, anti-obesity effect of MCHR1 antagonists directly exerted in BAT is proposed. Moreover, MCHR1 expression in murine brown adipocytes was confirmed by protein and mRNA analysis. We conclude that MCHR1 PET imaging contributes to basic research in endocrinology by elucidating the involvement of the MCH system in peripheral tissues, such as BAT.